Application of polyester derived from biomass in petroleum asphalt cement - Araújo,Fernando de (2017)
Abstract This study evaluated the effects of the incorporation of a new additive to asphalt cement oil (CAP). A polyol product was obtained through the oxypropylation reaction of sugarcane bagasse. This polyol was polymerised with pyromellitic anhydride in order to obtain a polyester (BCP) to test its suitability in terms of the material properties to be applied as additives. FTIR spectra of the polymerised material (BCP) confirmed the occurrence of chemical modification due to the appearance of a new band at 1750 cm-1, characteristic of ester groups. The TGA data showed that the BCP product had higher thermal stability than the polyol. According to the softening point and elastic recovery tests, the incorporation of 11% and 16% w/w BCP in conventional CAP met the specifications of regulatory standards.